Patients' experiences of behaviour change interventions delivered by general practitioners during routine consultations: A nationally representative survey. (4th March 2021) - Keyworth, Chris; Epton, Tracy; Goldthorpe, Joanna; Calam, Rachel; Armitage, Christopher J.
Abstract: Background: Consistent with the 'Making Every Contact Count' UK public health policy, general practitioners (GPs) are expected to provide patients with behaviour change interventions opportunistically. However, there is a belief widely held among GPs that patients neither want or need such interventions. We aimed to understand the following: (a) the characteristics of people attending GP appointments, (b) patients' needs for health behaviour change, (c) perceptions of appropriateness and helpfulness of interventions, and (d) factors associated with recall of receipt of interventions. Methods: Cross‐sectional nationally representative online survey of UK adults who had attended GP clinics in the preceding four weeks (n = 3028). Data were analysed using descriptive statistics and binary logistic regression. Results: 94.5% (n = 2862) of patients breached at least one health behaviour guideline, and 55.1% reported never having had a conversation with their GP about health behaviours. The majority of patients perceived intervention as appropriate (range 84.2%‐87.4% across behaviours) and helpful (range 82.8%‐85.9% across behaviours). Being male (OR = 1.412, 95% CI 1.217, 1.639), having a long‐term condition (OR = 1.514, 95% CI 1.287, 1.782) and a higher number of repeat GP visits (OR = 1.016, 95% CI 1.010, 1.023) were among factors associated with recall of receipt of interventions. Conclusions: Patients perceived behaviour change intervention during routine GP consultations as appropriate and helpful, yet there are variations in the likelihood of receiving interventions according to sociodemographic factors. GPs could adopt a more proactive approach to behaviour change in patient consultations with the broad approval of patients. Patient or public contribution: The questionnaire was piloted among a convenience sample prior to distribution.